Efficient electrosynthesis of sulfinic esters via oxidative cross‐coupling between alcohols and thiophenols. Issue 2 (9th September 2019) - Gong, Fengping; Lu, Fangling; Zuo, Lin; Wang, Qi; Li, Ru; Hu, Jiaxin; Li, Zhen; Takfaoui, Abdelilah; Lei, Aiwen
Abstract: A new protocol for SO bond formation was developed by electrochemical oxidative cross‐coupling between alcohols and thiophenols. With this strategy, a series of valuable sulfinic ester derivatives were synthesized up to 96% yield from basic starting materials. A preliminary mechanistic investigation reveals that this reaction involves oxygen reduction reaction (ORR). Abstract : A new protocol for SO bond formation was developed by electrochemical oxidative cross‐coupling between alcohols and thiophenols.